FoF1-ATP synthase/ATPase in the parasitic protist, Trypanosoma brucei - Šubrtová, Karolína (Jihočeská univerzita, 2015)
This thesis primarily focuses on the FoF1-ATP synthase/ATPase complex in the parasitic protist, Trypanosoma brucei. Instead of its normal aerobic function to synthesize ATP, it is required to hydrolyze ATP to maintain the m in the infective bloodstream stage of T. brucei and the related parasite, T. b. evansi. To better understand the composition, structure and function of this druggable target, my work focused on deciphering the function of three of the unique Euglenozoa specific subunits that comprise this complex molecular machine. Furthermore, the ADP/ATP carrier, which provides substrates for the FoF1-ATP synthase/ATPase, was functionally characterized and evaluated if it is physically associated with the complexes of the oxidative phosphorylation pathway.
FoF1-ATP synthase/ATPase in the parasitic protist, Trypanosoma brucei
Keywords: FoF1-ATP synthase; FoF1-ATPase; energy metabolism; oxidative phosphorylation; ADP/ATP carrier; Trypanosoma brucei; Trypanosoma brucei evansi; FoF1-ATP synthase; FoF1-ATPase; energy metabolism; oxidative phosphorylation; ADP/ATP carrier; Trypanosoma brucei; Trypanosoma brucei evansi